The Innovative Design of Deep In Situ Pressure Retained Coring Based on Magnetic Field Trigger Controller - Guikang Liu; Mingzhong Gao; Zhiwen Yang; Ling Chen; Maoquan Fu; Heping Xie (Advances in Civil Engineering)
Deep rock mass theory has not yet been completely established, which leads to a lack of theoretical guidance for deep resource development and poor continuity among engineering activities. The foundation of deep rock mechanics theory is to achieve the deep in situ rock fidelity coring (including the retaining of the pore pressure and temperature). To realize this, pressure-retaining coring technology is required. A self-triggered pressure-retaining controller based on magnetic control is proposed in this paper. The pressure-retaining controller realizes pressure-retaining coring in any direction by triggering the closure of the valve cover by a magnetic force, forming a magnetic seal. Fifteen combined magnetic circuit design schemes are proposed. The magnetic flux density norm distribution and magnetic force evolution law of different schemes are then quantitatively analyzed by the finite element method. The results show that a complex magnetization combination can weaken the nonlinear negative correlation between the magnetic force and distance. The optimal design of the valve seat magnetic circuit is Scheme 9, with the valve seat consisting of four shape identical tile magnets. Among the schemes, for Scheme 9, the magnetic flux density norm of the valve cover is the most concentrated. The maximum magnetic flux density norm is in the middle, and the magnetic force at 35 mm from the valve cover to the valve seat is 2.915 N. Scheme 9 satisfies the minimum condition of the mechanical model and verifies the feasibility of magnetic field triggering. This research can be used to gain a better understanding of deep Earth properties and provides technology for the improved design of deep in situ pressure-retaining coring devices.